Moral distress in nurses at an acute care hospital in Switzerland: Results of a pilot study. (February 2015) - Kleinknecht-Dolf, Michael; Frei, Irena Anna; Spichiger, Elisabeth; Müller, Marianne; Martin, Jacqueline S; Spirig, Rebecca
Background: In the context of new reimbursement systems like diagnosis-related groups, moral distress is becoming a growing problem for healthcare providers. Moral distress can trigger emotional and physical reactions in nurses and can cause them to withdraw emotionally from patients or can cause them to change their work place. Objective: The aim of this pilot study was to develop an instrument to measure moral distress among acute care nurses in the German-speaking context, to test its applicability, and to obtain initial indications of the instrument's validity. Method: The study was designed in 2011 as a cross-sectional pilot survey. Conducted on eight units of one university hospital in German-speaking Switzerland, 294 registered nurses were asked to fill out a web-based questionnaire on moral distress. Ethical considerations: The study proposal was approved by the cantonal ethics committee. All participating nurses provided informed consent and were assured of data confidentiality. Results: The survey had a response rate of 55%. The results show the prevalence of statements on the questionnaire indicating situations with the potential to trigger moral distress. The entire range of answers was used in the responses. Most participants found the questionnaire comprehensible, while some criticized the phraseology of certain statements. Many more found the registration process prior to online access to be too time consuming. Nurses confirmed that the results reflect their subjective assessment of their situation and their experience of moral distress. Conclusion: The newly developed moral distress questionnaire appears to produce face validity and is sufficiently applicable for use in our study. The results indicate that moral distress appears to be a relevant phenomenon also in Swiss hospitals and that nurses were experiencing it prior to the introduction of Swiss diagnosis-related groups.